2012
DOI: 10.1002/jbm.a.34502
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium incorporation into β‐TCP reduced itsin vivoresorption by decreasing parathormone production

Abstract: Beta-tricalcium phosphate (β-TCP), one of the most widely used bioresorbable materials for bone therapy, can be doped with magnesium ions, generating β-TCMP. The objectives of this work were to evaluate, on a murine dental alveolus grafting model, the biocompatibility of β-TCP and β-TMCP granules by histomorphometric analysis, as well as the impact on plasmatic levels of receptor activator of nuclear factor κB ligand (RANK-L), osteoprotegerin (OPG), osteocalcin, osteopontin, and parathormone (PTH) during bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…This occurs similarly with HA without Mg (Bertoni et al, 1998). The MgHA evaluated in our study showed, in the XRF analysis, a concentration of 0.47% Mg, 79% HA phase and 21% β-TCMP, and, nonetheless, the microspheres remained mostly intact at the end of the study, and did not present notorious biodegradation, in consonance with the results found by Yassuda et al (2013) and Sartori et al (2014), showing that the presence of Mg makes the ceramic biomaterials less bioresorbable, even in reduced concentrations. The microspheres implanted in GI showed a profile of biodegradation similar to GII, even without the presence of the metal.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This occurs similarly with HA without Mg (Bertoni et al, 1998). The MgHA evaluated in our study showed, in the XRF analysis, a concentration of 0.47% Mg, 79% HA phase and 21% β-TCMP, and, nonetheless, the microspheres remained mostly intact at the end of the study, and did not present notorious biodegradation, in consonance with the results found by Yassuda et al (2013) and Sartori et al (2014), showing that the presence of Mg makes the ceramic biomaterials less bioresorbable, even in reduced concentrations. The microspheres implanted in GI showed a profile of biodegradation similar to GII, even without the presence of the metal.…”
Section: Discussionsupporting
confidence: 91%
“…Bone neoformation was observed, in a similar way in groups I and II, beyond the borders, in the centripetal direction, in and around the microspheres. This suggests that the incorporation of Mg into the HA structure did not favor a greater osteogenic potential to the biomaterial, corroborating with the findings of Yassuda et al (2013), which evaluated β-tricalcium phosphate (β-TCP) substituted with Mg in rats, and Sartori et al (2014) who evaluated Mg-substituted HA in sheep, both in critical bone defect. Some studies suggest that Mg inhibits the formation of amorphous CaP within the synthetic HA structure given the introduction of distorted solid structures and the structural lag resulting from inhibition of crystal growth (Bigi et al, 1992(Bigi et al, , 1993Bertoni et al, 1998;Laurencin et al, 2011).…”
Section: Discussionsupporting
confidence: 75%
“…The reason why Mg stabilizes the structure of TCP may reside in the fact that Mg atoms are located closer to the axis of the cluster than the Ca atoms, due to their smaller ionic radius . Yassuda et al showed, in their in vivo study, that β‐TCP granules had a positive influence on osteoclast activity compared to β‐TCMP granules …”
Section: Resultsmentioning
confidence: 99%
“…Thus, for future works, the particle size and distribution should be better controlled in order to achieve a similar particle size and distribution among the groups. Beyond that, adding more water to the β‐TCMP and BCMP ink composition was necessary to adjust the ink rheology because Mg ions extend the dissolution behavior of calcium phosphates . Furthermore, the better mechanical behavior of β‐TCMP in comparison with the BCMP scaffolds could be a result of better particle packing, because the β‐TCMP powder had a multimodal distribution, whereas the BCMP powder had a unimodal one.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation